Epilepsy Diagnosis and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The incidence of a previous history of febrile convulsions (FC) and their relation to the diagnosis and localization of subsequent epilepsy were studied in 1005 patients presenting at the Epilepsy Clinic at Vanderbilt University, Nashville, TN.